Modification of carbohydrates of food raw materials in the process of thermoplastic extrusion (review) - A. Yu. Sharikov; M. V. Amelyakina (Аграрная наука Евро-Северо-Востока, 2021)
Extrusion can be considered not only as an effective technology for processing agricultural raw materials into feed and food products, but also as a thermo-mechanical method for modification of the chemical properties of biopolymers. Carbohydrates are the most represented class of organic compounds in raw materials processed by the agro-industrial complex. The assessment of the influence of the processing factor on the final physicochemical and technological properties of various types of carbohydrates included in the chemical composition of raw materials or used as mono-ingredients is an actual task for the food industry. The review considers the issues of extrusion modification of starch in terms of the difference in the properties of amylose and amylopectin as well as the presence of lipids and organic acids in the reaction system. Processes of macromolecular degradation, gelatinization, esterification and the formation of new chemical bonds in dependence on the conditions of extrusion and the composition of mixtures are discussed. The results of studies of the influence of extrusion cooking on the changes in the physicochemical properties of non-starchy polysaccharides, cellulose, araboxylans, inulin, pectin, chitosan, and gums of various origins are presented. It has been shown that extrusion and varying of its operating regimes can significantly affect the nutritional value of extrudates including changing the glycemic index, inactivating antinutritional factors, or increasing their content in extrudates.